MENYONGSONG PILKADA SERENTAK TAHUN 2024: TANTAGAN DAN PROSPEK DEMOKRASI LOKAL DI INDONESIA - Amri, Andi Miftahul (Jurnal Keadilan Pemilu, 2024)
This research aims to analyze the prospects for local democracy in Indonesia through the context of simultaneous Regional Head Elections (Pilkada) in 2024. Local democracy in Indonesia has experienced significant developments since the 1998 reforms, including the first simultaneous Pilkada which was held in 2015. Looking to the future, Simultaneous regional elections in 2024 have considerable potential in strengthening local democracy in Indonesia. The research method used is literature study or normative legal research which covers legal, political and social aspects of the constitution with the simultaneous regional election process. This research also involves collecting data on community participation, the role of the media, and voter involvement in the Simultaneous Regional Election process. The results of this research show that the simultaneous regional elections in 2024 could be an important momentum in strengthening local democracy in Indonesia. It is hoped that community participation in regional head elections will increase, as will community political understanding and awareness. Apart from that, the role of the media as a supervisor and supporter of the Pilkada process is also a key factor in ensuring transparency and accountability. However, this research also identifies several challenges faced in implementing the simultaneous regional elections in 2024. These challenges include political, economic and social factors that could influence.